Adult education in Spain during the blue period. From military victory to General Education Law (LGE) of 1970 - García Redondo, Eva (Historia y Memoria de la Educación, 2016)
The topic of this paper is to provide a critical review of adult education policies during the Franco period. By means of a historical-pedagogical method, clearly associated with the socio-historical approach, our work seeks to reveal the causes and the consequences of the policies, that is to say, both the reasons for the various initiatives aimed at this group as well as the social and political value derived from them. In this sense, we have undertaken an analysis of the role played by the Campaña Nacional de Alfabetización y Promoción Cultural de Adultos, which was understood to be the most ambitious project in the sociocultural field. By means of a simple but precise and clear hypothesis, we attempt to offer a realistic, accurate approach that seeks to add to the already revised view of the adult socio-educational vision during the dictatorship, offering a new analytical and interpretive point of view. To do so, we start from the well-documented Republican approach, which helps us to understand the evolution of adult education during the ensuing four decades of dictatorship.